(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3CHh GdRgQ Hf YHO Gddg Hf CHj GdRgQ GdESQGFjdi s)
(3ChdgG (B:s
(3bGd GdeDda CLeYJ gPG GdcJGH GdYXje GdaGFOI GdPi SejJg HcJGH GdJUQja ai GdCOhjI GdeQcHI hCcedJ LejY ebGdGJg s
(3BNQgG (B:s
(3JeJ GdebGdI ai Yed GdjO GdJi gi NGJeI GdcJGH s
(3fSNI SGOSIs
(3hHGdfSNI QShe hCTcGd dCOhGJ GdLQGMIs
(3hHYV GdChQGb aGSOI ai GdJUhjQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs